Using Small Group Discussion in Teaching Reading Comprehension - Muhammad Ilham Muslim; Asnawi Muslem; Diana Fauzia Sari (Universitas Syiah Kuala, 2022)
The research is conducted to find out whether the use of Small Group Discussion is effective to improve students’ reading comprehension. It also investigates the type of motivation used by the students in learning English. This research employs quantitative method in nature. The population of this research is all the second grade students of State Junior High School 2 Ingin Jaya Aceh Besar. The samples of the research are 30 students of the Second Grade selected purposively from the previously mentioned population. The instruments used in this research are test and a set of questionnaire. Pre-test of reading comprehension is given before the treatment, while post-test was conducted after the treatments were completed.. Lastly, a set of questionnaire is distributed to the students to see their types of motivation in learning English. The data collected were analyzed using statistical inference. The results suggested that the use of Small Group Discussion was effective to improve students’ reading comprehension. It was discovered that the Small Group Discussion method is effective in improving the students’ reading comprehension of descriptive text (P-Value of 0,002 (P0,05)). The results also revealed that the students had a stronger integrative motivation (4,10) compared to instrumental motivation (3,76). It can be concluded that Small Group Discussion can improve the students’ reading comprehension and motivation.